The First Meta-Analysis of the M129V Single-Nucleotide Polymorphism (SNP) of the Prion Protein Gene (PRNP) with Sporadic Creutzfeldt–Jakob Disease - Yong-Chan Kim (MDPI AG, 2021)
Prion diseases are fatal, chronic, and incurable neurodegenerative diseases caused by pathogenic forms of prion protein (PrPSc) derived from endogenous forms of prion protein (PrPC). Several case–control and genome-wide association studies have reported that the M129V polymorphism of the human prion protein gene (PRNP) is significantly associated with susceptibility to sporadic Creutzfeldt–Jakob disease (CJD). However, since some case–control studies have not shown these associations, the results remain controversial. We collected data that contain the genotype and allele frequencies of the M129V single-nucleotide polymorphism (SNP) of the PRNP gene and information on ethnic backgrounds from sporadic CJD patients. We performed a meta-analysis by collecting data from eligible studies to evaluate the association between the M129V SNP of the PRNP gene and susceptibility to sporadic CJD. We found a very strong association between the M129V SNP of the PRNP gene and susceptibility to sporadic CJD using a meta-analysis for the first time. We validated the eligibility of existing reports and found severe heterogeneity in some previous studies. We also found that the MM homozygote is a potent risk factor for sporadic CJD compared to the MV heterozygote in the heterozygote comparison model (MM vs. MV, odds ratio = 4.9611, 95% confidence interval: 3.4785; 7.0758, p < 1 × 10−10). To the best of our knowledge, this was the first meta-analysis assessment of the relationship between the M129V SNP of the PRNP gene and susceptibility to sporadic CJD.